Breast Units in Europe – Certification in 9 European Countries 9 Years after the European Society of Mastology Position Paper - Taran, F. Andrei (S. Karger GmbH, 2009)
SUMMARY: INTRODUCTION: We aimed to take a snapshot of breast units in the European Union 9 years after the publication of the European Society of Mastology (EUSOMA) position paper. METHODS: In order to obtain information on breast units throughout the European Union, we designed a questionnaire comprising 5 questions on certification, audit frequency and number of breast units in each country. Our primary contacts were national cancer societies, breast cancer study groups, breast cancer organizations, national associations and societies of breast treatment, as well as experts in the field of breast cancer. RESULTS: Information on characteristics of the certification process and number of breast units was obtained for 9 countries of the European Union. 7 of the 9 countries (78%) have a certification process of the breast units. Certification is carried out by public authorities in 4 (57%) countries and by private companies in 3 (43%) countries. Information on frequency of auditing was reported in 4 countries and varied between annual audits (Austria, Ireland and Germany) and audits once every 3 years (United Kingdom). CONCLUSIONS: The current study suggests that the European breast unit landscape is a heterogeneous field. 9 years after the EUSOMA position paper, we do not have any standard European guidelines, neither for the development nor for the mandatory prerequisites of a breast unit. The development and operation of breast units are still country specific.